Where Art and Science meet - Plant Collections from the 19th century - Sárospataki, Máté (4D Journal of Landscape Architecture and Garden Art, 2011)
There are various names to designate living collections of ligneous plants. Some of these terms are defined exactly in special literature, but no comprehensive study has been written that analyses the terms related to 19th century plant collections one by one and in correlation with each other from the viewpoint of landscape architecture.